2016
DOI: 10.5194/hess-2016-536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate change and uncertainty in high-resolution rainfall extremes

Abstract: Abstract. A methodology to analyze the impact of climate change on rainfall extremes with a high temporal resolution is presented. It is based on a rainfall stochastic simulator which consists of a point process model for the daily scale (Neymann-Scott Rectangular Pulse Model) and a nested disaggregation scheme for the 10-min rainfall scale (Multiplicative Random Cascade Model). Climate change signals are included as Factors of Change applied to key statistics (first–third order moments, correlation and interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(67 reference statements)
1
2
0
Order By: Relevance
“…Since rainfall and hydrologic performance are linked, changes in rainfall caused by climate change are also expected to alter the ability of green infrastructure to reduce combined sewer overflows, mitigate urban runoff, or comply with stormwater management regulations. Findings from prior research, primarily focused on changes in GSI discharge quality, are consistent with other climate impacts studies that illustrate that future impacts are deeply uncertain and depend on the climate change scenario used in modeling (Cook et al, 2017;Hall, 2014;Kianfar et al, 2016;Musau et al,). Zhang et al (2019) evaluated the pollution treatment performance of constructed wetlands and found notable differences in performance when different climate models were used.…”
Section: Introductionsupporting
confidence: 75%
“…Since rainfall and hydrologic performance are linked, changes in rainfall caused by climate change are also expected to alter the ability of green infrastructure to reduce combined sewer overflows, mitigate urban runoff, or comply with stormwater management regulations. Findings from prior research, primarily focused on changes in GSI discharge quality, are consistent with other climate impacts studies that illustrate that future impacts are deeply uncertain and depend on the climate change scenario used in modeling (Cook et al, 2017;Hall, 2014;Kianfar et al, 2016;Musau et al,). Zhang et al (2019) evaluated the pollution treatment performance of constructed wetlands and found notable differences in performance when different climate models were used.…”
Section: Introductionsupporting
confidence: 75%
“…At plot scale,Xia et al (2013) showed that, for cropland in China, I 10 , I 20 , I 30 , or I 60 were significantly correlated with event losses of N and P and offered some hypotheses about why one or another index of intensity should become significant at a particular field site Nunes et al (2011). also stressed the explanatory power of I 10 and I 60 for erosion under various cover types in Portugal, as didKiassari et al (2012) for erosion plots in semi-arid Iran.…”
mentioning
confidence: 90%
“…A common approach to the analysis of extreme rainfall intensities is the use of downscaling from daily maxima to sub-daily values, though this is normally only extended to the prediction of hourly maxima. Sub-hourly rainfall data are generated in some canonical cascade downscaling models (Kianfar et al 2016, Haddad & Rahman 2014, Paschalis et al 2014, Pohle et al 2018) though with only moderate success in generating realistic intensities. As noted by Forestieri et al (2018) downscaling can be undertaken by using correlations between daily and sub-daily maxima established from historical data, on the presumption that the correlations will remain invariant under climate change.…”
Section: Short-term Intensity Bursts and Climate Changementioning
confidence: 99%